Exome sequencing and prenatal skeletal abnormalities: comprehensive review and meta-analysis and way forward - Jiang, Mengting; Zhang, Bin; Wang, Jing; Wei, Cui; Mao, Xiuzhen; Yu, Bin (Frontiers in Genetics, 2025)
ObjectiveTo assess the detection rate of exome sequencing (ES) in fetuses diagnosed as skeletal abnormalities (SKA) with normal karyotype or chromosomal microarray analysis (CMA) results.MethodsWe conducted electronic searches in four databases, focusing on studies involving ES in fetuses with SKA. Additional detection rate of ES compared to karyotype/CMA was calculated, followed by a meta-analysis. Subgroup analyses explored the influence of fetal phenotype on diagnostic outcomes.ResultsFrom 2,393 studies, 21 reports covering 476 fetuses were analyzed. Key findings include: (1) an additional detection rate of ES of 63.2% (Risk Difference (RD), 0.68 [95% CI, 0.60–0.76], p < 0.00001); (2) identification of 76 genes across 304 types of variants, with FGFR3, COL1A1, COL1A2, and COL2A1 being prevalent; (3) lower detection rates in fetuses with isolated short long bones compared to non-isolated conditions, though not significantly different (p = 0.35); (4) higher detection rates in subgroups with abnormal ossification, small chest, suspected long bone fractures or angulations, and skull abnormalities.ConclusionThe meta-analysis indicates that genetic variation significantly contributes to fetal SKA, primarily due to single-gene variants. Consequently, ES should be used in the prenatal diagnosis of SKA fetuses in clinical practice.